Peningkatan Kemampuan Mengenal Nilai Tempat Bilangan Melalui Model Pengajaran Langsung bagi Anak Berkesulitan Belajar Kelas II SD N 18 Koto Luar Padang - Reuni Wisudawaty (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract: This research is back grounded by the problem which is found at SD N 18 Koto Luar Padang. Three children difficult in learning from 2nd grade got a problem in knowing place values of numbers. Capability of children was very low. Base on it, this research is aimed to prove the escalation capability of place values of numbers for the children difficult in learning.This research uses experiment appoach in Single Subject Design form by multiple baselines cross subjects design. Data was analyzed by visual graph analysis. Assessment in this research uses the entry of total question data that right-answered by using frequency.The result of this research shows that the capability of children in knowing place values of numbers increased. The observation had been done thirteen times for every subject. In the first subject IK baseline data low stable and mean level 1,16. Intervention condition, mean level 11,85 and trend increased. Subject JE baseline, data low stable and mean level 0,66. Intervention condition, with mean level 11,42 trend increased. Subject Z baseline data is low stable and mean level 1. Intervention condition, mean level 11,42 trend increased. As we can see from the changes of data analysis between condition of subject X with B/A condition is +3. Subject JE at B/A condition is +6. Subject ZI at B/A condition is +5. Base on the result of the research, we conclude the direct instruction can increase the capability of knowing place values of numbers of 2nd grade at SD N 18 Koto Luar Padang.Keyword: Children  difficult in learning, place values of numbers, direct instructionPendahuluan